2008
DOI: 10.1007/s00436-008-1249-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile, localization of an 8-kDa calcium-binding protein from Schistosoma japonicum (SjCa8), and vaccine potential of recombinant SjCa8 (rSjCa8) against infections in mice

Abstract: Researches on genes expressed in a cercarial stage-specific manner may help us understand the molecular events and functions during schistosome invasion of skin. A genomic clone encoding 8-kDa calcium-binding protein (SjCa8) specifically expressed in cercariae and skin-stage schistosomulum (transformed within 3 h) was obtained from cercariae. Recombinant protein was expressed in vector pET32a (+) and purified using a Ni-NTA purification system. The target protein SjCa8 was determined by matrix-assisted laser d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Purification was done by Ni-NTA under denaturing condition. His-tag was employed in the purification of recombinant proteins based on immobilized metal affinity chromatography, which has been used in a number of studies (Kim et al 2007;Lv et al 2009). The result indicated that the above mentioned conditions were appropriate for the purification and refolding of apyrase protein.…”
Section: Discussionmentioning
confidence: 99%
“…Purification was done by Ni-NTA under denaturing condition. His-tag was employed in the purification of recombinant proteins based on immobilized metal affinity chromatography, which has been used in a number of studies (Kim et al 2007;Lv et al 2009). The result indicated that the above mentioned conditions were appropriate for the purification and refolding of apyrase protein.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of linalool on integrity of the cercarial tegument was evaluated using detection of tegumentary protein SjCa8, a cercariae specific molecule, which has been described by Lv et al [19]. Briefly, after treatment with different compound for 30 min, and subsequent three washes (5 min each) with 1 × PBS, cercariae were incubated for 45 min at 37°C in PBS containing 5% bovine serum albumin (BSA, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, after treatment with different compound for 30 min, and subsequent three washes (5 min each) with 1 × PBS, cercariae were incubated for 45 min at 37°C in PBS containing 5% bovine serum albumin (BSA, Sigma). The worms were treated for 45 min at 37°C with the primary antibodies (1:500 dilution) to recombinant SjCa8 prepared in our laboratory [19]. After an additional washing step, parasites were incubated for 1 h at room temperature with Cy3-conjugated anti-mouse IgG diluted at 1:100, washed thrice and then observed under an FV 500-IX81 laser scanning confocal system (Olympus, Japan) with Krypton/Argon laser and appropriate filters.…”
Section: Methodsmentioning
confidence: 99%
“…One week after the final booster dose, mice were bled, and the antiserum was collected. Blood samples from C57BL/6 mouse infected with S. japonicum and normal mouse serum were prepared as our previous study (Lv et al 2009). All sera were separated by centrifuging the blood samples at 4°C (10,000 rpm, 20 min) and stored at −70°C until use.…”
Section: Mouse Sera Preparationmentioning
confidence: 99%